2015
DOI: 10.1080/02786826.2015.1047012
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Aircraft Engine Non-Volatile PM Emissions: Results of the Aviation-Particle Regulatory Instrumentation Demonstration Experiment (A-PRIDE) 4 Campaign

Abstract: This study reports the first of a kind data on aircraft engine non-volatile particulate matter (nvPM) number-and massbased emissions using standardized systems. Two compliant sampling and measurement systems operated by Missouri University of Science and Technology (Missouri S&T) and Empa were evaluated during the Aviation-Particle Regulatory Instrumentation Demonstration Experiment (A-PRIDE) 4 campaign at the SR Technics facilities in Z€ urich, Switzerland, in November 2012. The Missouri S&T and Empa systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
134
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(163 citation statements)
references
References 32 publications
18
134
1
Order By: Relevance
“…In the case of large amounts of volatile material, the mass of volatile material greatly outweighs the mass of soot, the particle becomes spherical, and the effective density approaches the material density of the volatile material. Lobo et al (2015) used a similar dilution system (with dilution ratio of ~10) and their effective density data is similar to the measurements from the Gnome engine. On the other hand, Abegglen et al (2015) and Durdina et al (2015) did not dilute their sample for the majority of their tests but used a dryer to remove water from the aerosol.…”
Section: Effective Density: Relationship Between Particle Mass and Momentioning
confidence: 59%
See 4 more Smart Citations
“…In the case of large amounts of volatile material, the mass of volatile material greatly outweighs the mass of soot, the particle becomes spherical, and the effective density approaches the material density of the volatile material. Lobo et al (2015) used a similar dilution system (with dilution ratio of ~10) and their effective density data is similar to the measurements from the Gnome engine. On the other hand, Abegglen et al (2015) and Durdina et al (2015) did not dilute their sample for the majority of their tests but used a dryer to remove water from the aerosol.…”
Section: Effective Density: Relationship Between Particle Mass and Momentioning
confidence: 59%
“…Lobo et al (2015) used a similar dilution system (with dilution ratio of ~10) and their effective density data is similar to the measurements from the Gnome engine. On the other hand, Abegglen et al (2015) and Durdina et al (2015) did not dilute their sample for the majority of their tests but used a dryer to remove water from the aerosol. (In comparison tests, Durdina et al (2015) found that at high thrust the effective densities of diluted and undiluted samples were similar).…”
Section: Effective Density: Relationship Between Particle Mass and Momentioning
confidence: 59%
See 3 more Smart Citations